THE CONSTRUCTIVISTIC COMPETENCE BASED LEARNING DEVELOPMENT OF ENTREPRENEURSHIP CLASS - Maskan, Mohammad; Djajanto, Ludfi; Utaminingsih, Alifiualhtin (Journal of Innovation in Business and Economics, 2017)
This study focused on development learning of the entrepreneurship learning model into learning model characterized by constructivistic learning, in which this learning model employs students who are active, multi methods of teaching, and multi source of learning. Findings show that the product of construvtivistic based entrepreneurship learning model is good. It means that product of portfolio-based entrepreneurship learning model is valid to use in the learning process of entrepreneurship lesson at Business Administration Department of Malang State Polytechnic. It is recommended that (1) lecturers who are teaching lesson of entrepreneurship should be given provision about constructivistic-based entrepreneurship learning model, and (2) For further development, this entrepreneurship learning model can be applied in other lessons.